Chest wall lymph node metastasis from follicular thyroid carcinoma: a rare case report - Taolang Li; Zhiyuan Ma; Chengli Lu; Quanzhong Zhou; Zelong Feng; Xinglong Wu; Yi Luo; Dan Li; Xiaoming Cheng; Xuemei Liu (BMC, 2019)
Abstract Background Distant metastases from follicular thyroid carcinoma are mainly hematogenous and are commonly observed in the lungs and bones. Other rare sites are the parotid gland, skin, brain, ovary, adrenal gland, kidney, pancreas and breast, with chest wall lymph node metastasis being even more rare. Case presentation Over the past 10 years, three surgeries were performed on a 69-year-old women with a history of follicular thyroid cancer and its metastatic lesions. The patient presented with a 3-month history of masses in the left chest. She underwent detailed examination of the chest wall tumors, and surgery was then performed to resect all of the tumors. Based on the histopathology, these lymph nodes were confirmed to harbor metastatic follicular thyroid carcinoma. Conclusion This study reports the first case of follicular thyroid carcinoma metastasis to the chest wall lymph node.